Understanding How Experts Do It: A Conceptual Framework for the Open Transversus Abdominis Release Procedure. Issue 3 (17th March 2023) - Grover, Karan; Korenblit, Nechama; Babu, Archana; Podolsky, Dina; Carbonell, Alfredo; Orenstein, Sean; Pauli, Eric M.; Novitsky, Yuri; Madani, Amin; Sullivan, Maura; Nieman, Dylan
Abstract : Background: The safe and effective performance of a posterior component separation via a transversus abdominis release (TAR) requires intraoperative judgement and decision-making skills that are difficult to define, standardize, and teach. We herein present the first qualitative study which builds a framework upon which training and objective evaluation of a TAR can be based. Methods: Hierarchical and cognitive task analyses for a TAR procedure were performed using semistructured interviews of hernia experts to describe the thoughts and behaviors that exemplify optimal performance. Verbal data was recorded, transcribed, coded, and thematically analyzed. Results: A conceptual framework was synthesized based on literary sources (4 book chapters, 4 peer-reviewed articles, 3 online videos), 2 field observations, and interviews of 4 hernia experts [median 66 minutes (44–78)]. Subject matter experts practiced a median of 6.5 years (1.5–16) and have completed a median of 300 (60–500) TARs. After 5 rounds of inductive analysis, 80 subtasks, 86 potential errors, 36 cognitive behaviors, and 17 decision points were identified and categorized into 10 procedural steps (midline laparotomy, adhesiolysis, retrorectus dissection, etc.) and 9 fundamental principles: patient physiology and disease burden; tactical modification; tissue reconstruction and wound healing; task completion; choice of technique and instruments; safe planes and danger zones; exposure, ergonomics, environmental limitations; anticipation and forward planning; and tissue trauma and handling. Conclusion: This is the first study to define the key tasks, decisions, and cognitive behaviors that are essential to a successful TAR procedure.